EMPOWERMENT STRATEGY FOR RICE FARMERS' INSTITUTIONS IN RIAS VILLAGE, SOUTH BANGKA REGENCY USING SWOT - QSPM APPROACH - Pagondo, Efendi H; Reniati; Nugroho, Ari Agung (International Journal of Economics, Business, and Entrepreneurship, 2024)
The purpose of this research is to formulate an empowerment strategy for rice farmer institutions in Rias Village, South Bangka Regency. The research method is qualitative. The sampling technique is done purposively, and data is collected through interviews. Strategy analysis and formulation are conducted using the SWOT-QSPM approach. Through the SWOT-QSPM analysis, priority strategies are formulated to improve the performance and capacity of farmer groups in managing agricultural enterprises and expanding markets. The SWOT-QSPM recommendations include the development of collaboration, productivity enhancement of rice, optimization of information technology, financial strengthening, risk management, and continuous evaluation.